New crystal structure of the proteasome-dedicated chaperone Rpn14 at 1.6 Å resolution - Kim, Sangwoo (International Union of Crystallography, 2012)
The 26S proteasome is an ATP-dependent protease responsible for selective degradation of polyubiquitylated proteins. Recent studies have suggested that proteasome assembly is a highly ordered multi-step process assisted by specific chaperones. Rpn14, an assembly chaperone for ATPase-ring formation, specifically recognizes the ATPase subunit Rpt6. The structure of Rpn14 at 2.0 Å resolution in space group P6(4) has previously been reported, but the detailed mechanism of Rpn14 function remains unclear. Here, a new crystal structure of Rpn14 with an E384A mutation is presented in space group P2(1) at 1.6 Å resolution. This high-resolution structure provides a framework for understanding proteasome assembly.